Reflections on the importance of fieldwork for studies in Environmental Sciences (Research, Society and Development, 2020)
In view of the current problems of exploration and environmental degradation, there is no denying that the Environmental Sciences are gaining more and more prominence in research developed around the world, mainly in Brazil. Because it is an area that seeks to clarify questions existing in the relationship between man and nature, from the molecular level to the relationships that species establish with the environment they are inserted in. This study was carried out in order to obtain an overview regarding the importance of experimental fieldwork for the Environmental Sciences area, addressing issues such as environmental sciences in Brazil, national scientific research, general and fundamental aspects of field work and the importance of this practice for this area. The methodology used was a qualitative bibliographic study of articles and publications related to the central theme. On-site activities play an extremely important role in the training of students and researchers, allowing them to build dynamic training, where theory and practice work together in the construction of knowledge and in their personal and professional training. Encouraging the practice of field studies is fundamental in the development of quality and significant research for the country, in addition to directly impacting on the construction of new environmental perspectives.